Comparison of the characteristics of suicide attempters with major depressive disorder and those with no psychiatric diagnosis in emergency departments of general hospitals in China - Shengnan Wei; Haiyan Li; Jinglin Hou; Wei Chen; Xu Chen; Xiaoxia Qin (Annals of General Psychiatry, 2017)
Abstract Background Major depressive disorder (MDD) is a known major risk factor for suicide due to the high suicide mortality. However, studies comparing the characteristics of suicide attempters with major depressive disorder and those with no psychiatric diagnosis in China are very limited. This study examined and compared the sociodemographic and psychological characteristics of suicide attempters with MDD and those with no psychiatric diagnosis in emergency departments of general hospitals to better understand the risk factors for suicide attempts in China. Methods All subjects were enrolled in the study between June 2007 and January 2008. A total of 127 suicide attempters—54 with MDD and 73 with no psychiatric diagnosis—were enrolled. The sociodemographic and clinical characteristics were compared between two groups using the statistical analysis performed using frequency distribution, Student’s t test, Chi-square test, and Fisher’s exact test and a logistic regression model. Results Suicide attempters with MDD were more likely to be more depressive, older, divorced or separated, unemployed, and living alone, and more likely to write a suicide note, have suicide ideation, and be motivated by reducing pain and burden. Suicide attempters with no psychiatric diagnosis were more likely to be younger and more impulsive, have self-rescue, and be motivated by threatening or taking revenge on others. Multivariate logistic regression analysis identified the following independent predictors of suicide attempts in individuals with MDD: a lower score on the quality of life scale, more years of education, and suicide ideation. Conclusions The present study found both similarities and differences in the sociodemographic and clinical characteristics of suicide attempters with MDD and those with no psychiatric diagnosis in the emergency departments of general hospitals in China. These findings will help us to recognize the characteristics of suicide attempters in both groups and develop specific interventions for the two types of suicide attempters to prevent future suicide in China. For example, the suicide attempters with MDD in the emergency departments must be advised to the psychological clinic.